Effect of organic zinc supplementation into basal diets on productive performance of laying hens - B. M. W. Al-Obaidi; E. K. Mahmood; M. A. Alnoori; H. M. Alnori; O. A. Saeed (Journal of the Indonesian Tropical Animal Agriculture, 2022)
This study was carried out to determine the dietary supplementation of organic zinc on feed intake (FI), feed conversion ratio (FCR), egg production (EP), egg mass (EM) and quality. A total of 120 ISA-Brown layers aged 20 weeks were used in this study. Hens were distributed randomly to four treatments (30 hens of each) with three replicates. The organic zinc was supplemented into basal diet at different concentrations as follows; (T1) 0, (T2) 100, (T3) 200, and (T4) 300 mg/kg. The results showed T2 was recorded improvement significant on FI, and FCR followed by T3. Also, egg mass in T2 was increased significantly compared with T1. The T2 and T3 were significantly higher in average egg production as compared to T1 which was showed the lowest value. There was no significant effect on egg quality when supplemented organic Zn to the diet of layer hens. It might be concluded that the dietary supple-mentation of 100 mg/kg of organic Zn has improved feed consumption which is reflected in the produc-tivity of laying hens.